Black rat invasion of inland Sahel: insights from interviews and population genetics in south‐western Niger. (2nd July 2016) - Berthier, Karine; Garba, Madougou; Leblois, Raphael; Navascués, Miguel; Tatard, Caroline; Gauthier, Philippe; Gagaré, Sama; Piry, Sylvain; Brouat, Carine; Dalecky, Ambroise; Loiseau, Anne; Dobigny, Gauthier
Abstract : Human population migrations, as well as long‐distance trade activities, have been responsible for the spread of many invasive organisms. The black rat, Rattus rattus, has colonized most of the world following ship‐mediated trade. Owing to its tight association with human infrastructures, this species has been able to survive in unfavourable environments, such as Sahelian Africa. In this work, we combined interview‐based and population genetic surveys to investigate the processes underlying the ongoing invasion of south‐western Niger by black rats, with special emphasis on the capital city, Niamey. Our trapping and interview data are quite congruent, and all together point towards a patchy, but rather widespread, current distribution of R. rattus . Genetic data strongly suggest that road network development for truck‐based commercial flow from/to international harbours located in neighbouring countries (Benin, Togo, and Nigeria) facilitates the passive dispersal of black rats over a long distance through unfavourable landscapes. Another potentially, more ancient, invasion route may be associated with boat transport along the Niger River. Human‐mediated dispersal thus probably allows the foundation of persisting populations within highly anthropized areas while population dynamics may be more unstable in remote areas and mostly depends on propagule pressure.